2014
DOI: 10.2108/zs130149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recovery Method and Centrifugation on Epididymal Sperm from Collared Peccaries (Pecari tajacuLinnaeus, 1758)

Abstract: In order to establish protocols for gamete recovery from accidentally killed wild animals, or to take advantage of those slaughtered by captive breeders, we assess the influence of two methods on the recovery of epididymal sperm from collared peccaries, and verify the effect of centrifugation on such gametes. Genitalia from nine animals were used. For each animal, one epididymis was processed by flotation and the other was processed by retrograde flushing, both using a buffered media based on Tris. Following r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We observed that both flotation and retrograde flushing methods proved to be effective for sperm recovery in this species, similarly as reported for collared peccaries ( Pecari tajacu ; Bezerra et al . ). On the other hand, we highlight the ease and convenience at conducting the flotation for epididymal sperm recovery in this rodent, given the small size of its epididymis.…”
Section: Discussionmentioning
confidence: 97%
“…We observed that both flotation and retrograde flushing methods proved to be effective for sperm recovery in this species, similarly as reported for collared peccaries ( Pecari tajacu ; Bezerra et al . ). On the other hand, we highlight the ease and convenience at conducting the flotation for epididymal sperm recovery in this rodent, given the small size of its epididymis.…”
Section: Discussionmentioning
confidence: 97%
“…After slaughtering, the testis–epididymis complexes (CTEs) were removed, covered with gauze humidified with sterile salt solution (NaCl 0.9%), and immediately transported to the laboratory at room temperature. The CTEs were dissected and cauda epididymis, including 4 to 5 cm of the proximal vas deferens, were isolated and washed with salt solution to remove blood and cell debris (Bezerra et al ., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, studies on peccaries’ germplasm conservation have been mainly focused on the use of ejaculated sperm (Castelo et al ., 2010a; Silva et al ., 2012; Souza et al ., 2016; Campos et al ., 2017) and there has been only one study concerning the recovery and characterization of their epididymal sperm (Bezerra et al ., 2014). The use of epididymal sperm represents an important tool for their conservation because it allows the preservation of genetic material from valuable wild and captive individuals, even in the event of an unexpected death (Vilela et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the retrograde washing is accomplished by injecting a buffered solution at the vas deferens, as it was described for the agouti [21]. In some species, such as collared peccaries [22] and yellow-toothed cavies (Galea spixii) [23], both recovery methods can be conducted with no notorious differences on sperm quality.…”
Section: Epididymal Sperm Retrievalmentioning
confidence: 99%